Tax Avoidance and Its Implications on the Cost of Debt: Evidence from the Indonesian Property and Real Estate Sector - Mohammad Caesar (Journal Of Economic Cluster, 2026)
Tax avoidance is a legal strategy used by companies to reduce tax liabilities by exploiting loopholes in tax regulations. Meanwhile, the cost of debt reflects the costs that companies must bear for using debt. This study aims to analyze the effect of tax avoidance on the cost of debt in property and real estate companies listed on the Indonesia Stock Exchange (IDX) in the 2021–2023 period. This study uses a quantitative method with secondary data from the financial statements of 13 property and real estate companies listed on the IDX. Data analysis techniques include classical assumption tests, simple linear regression analysis, and hypothesis testing using SPSS software version 24. The results show that tax avoidance has no significant negative effect on the cost of debt, with the calculated t-value (-0.773) smaller than the t-table (2.006) and a specific significance level (p-value = 0.443). In addition, the coefficient of determination (R2) value of 0.012 indicates that tax avoidance only explains 1.2% of the variation in the cost of debt, while 98.8% is influenced by other factors. This conclusion indicates that tax avoidance strategies do not significantly affect the company's cost of debt. This occurs because creditors in the capital-intensive property sector tend to ignore tax strategies and focus more heavily on hard assets or physical collateral to mitigate default risks, making corporate tax avoidance less relevant in debt pricing decisions.